Effect of bubble trailing vortex on coal slime motion in flotation. (15th February 2023) - Pan, Gaochao; Zhu, Hongzheng; Shi, Qinghui; Zhang, Yong; Zhu, Jinbo; Ou, Zhanbei; Gao, Lei
Highlights: Relative height of low-velocity region fitted well with Re of a correlation coefficient 0.931. Separation angle showed a good mathematical relationship to the fluid flow velocity with a correlation coefficient of 0.991. Horizontal forces acting on the coal particle was analyzed to support the particle trajectory around the trailing vortex region. Abstract: Understanding the coal slime motion around the trailing vortex is an important precursor for predicting the entrainment probability of the bubble trailing vortex in coal flotation. Using a particle image velocimetry (PIV) system, we investigated the length of low-velocity region and the separation behavior of liquid from the cylinder surface under different fluid flow velocities. As the average fluid flow velocity increased, the height of the low-velocity region firstly increased and then gradually decreased, while the separation angle firstly decreased rapidly and then be almost constant at 94.2°. The relative height of low-velocity region and the separation angle fitted well with the fluid flow velocity, respectively. The trajectory of the coal particle having a diameter of 0.1875 mm moved around the cylinder was explored via a high-speed camera system. The coal particle first moved against the cylinder surface and then entered the trailing vortex region, where the centrifugal force and dynamic pressure provided sufficient energy. After a similar circular motion, the coal particle left the region relying on the dynamic pressure. Our results can provide a valuable insight into the development of technology for cleaner mineral flotation.